Design process of the Japanese pavilion in Venice Biennale (1956) by Takamasa Yoshizaka - Yoshito Tomioka; Chikako Tabata; Tomoya Ojika (Japan Architectural Review, 2023)
Abstract The objectives of this study were to reconstruct the design process of the Japanese pavilion in Venice Biennale, Italy (1956) designed by Takamasa Yoshizaka and to reveal the architect's formal manipulations and underlying strategic design thinking. The study materials are the original design sketches held in the National Archives of Modern Architecture, Tokyo, Japan. Initially, the chronological order of the design sketches was established by inspecting their dates and analyzing their formal similarities. The transformability (variations or changes of architectural form presented in a certain state of design) was analyzed and interpreted through a series of “studies” (partial problem‐solving processes). Finally, the architect's formal manipulations were reconstructed and presented and his relevant design intentions were revealed.